Gerenciamento de impressões, crise macroeconômica decorrente da covid-19 e representação feminina nas empresas brasileiras de capital aberto - Leoncio, Yohanna Jade dos Santos (2024)
Impressions of Management (IM) is defined as a set of strategies used by individuals to control how others perceive them. This phenomenon was initially discussed in the context of social psychology and later extended to the business environment, where organizations seek to enhance their image or mitigate the impact of a negative action for which they are responsible to stakeholders in order to preserve their reputation and ensure organizational legitimacy. This practice can be influenced by numerous situational variables, including the macroeconomic context in which the organization operates. Despite the extensive literature that addresses the relationship between GI and macroeconomic crisis, the empirical results presented in these studies are divergent, making discussions on the topic inconclusive. Given the diversity of results found, it is discussed whether other variables may affect this relationship, such as the representation of women in senior management, since women are generally less likely to manipulate corporate information due to personal characteristics such as ethical and transparent behavior. Therefore, the question arises as to the possibility of female representation in senior management interfering with the relationship between GI and crisis. In this context, this research aims to analyze the relationship between GI, the macroeconomic crisis resulting from the Covid-19 pandemic and female representation in senior management in companies listed on Brasil, Bolsa, Balcão (B3). This study is characterized as descriptive, using a quantitative approach, and collects a sample of B3-listed companies that issued earnings releases from 2017 to 2021, covering the period before and during the Covid-19 pandemic. Data were collected from the CVM atabase, Economática®, and the companies' reference forms. escriptive statistics, correlation analysis and multiple linear regression techniques with panel data were used. The results of the research showed a statistically significant and positive relationship between the GI and the macroeconomic crisis caused by the Covid-19 pandemic, reducing the fact that the GI level is higher during periods of economic instability. A pattern of a tendency towards an optimistic tone was also observed. Furthermore, no evidence was found of the existence of a negative relationship between GI and female representation in senior management, nor that female representation in senior management can weaken the GI-CRISIS relationship, minimizing this practice.